Improving Learning Outcomes for Volleyball Passing Through the Application of the Demonstration Method - Aksaruddin; Liliana Puspa Sari; Rinaldi Aditya (LPPM Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2020)
This study aims to find out how to improve learning outcomes Passing on the Volleyball game through the Demonstration Method in Class V Students of Alur Tani Elementary School, Aceh Tamiang District, 2019/2020 Academic Year. The object in this study were students of Class V with a total of 30 students consisting of 12 male students and 18 female students who would be given action in the form of using the Demonstration Method to the learning outcomes of Passing above. Based on the results of student learning in the first cycle, the first learning outcomes test was carried out, it can be seen that the initial ability of students in performing the ball passing technique was still low. Of the 30 students, there were 20 people (66%) who had achieved mastery learning, while 10 people (34%) had not yet achieved mastery learning. The average value of student learning outcomes is 76.3. Whereas in cycle II it can be seen that the students' ability to test classical learning outcomes has increased. Of the 30 students, there were 26 students (86.2%) who had achieved mastery learning, while 4 people (13.8%) had not yet achieved mastery learning. The average value of student learning outcomes is 80.7, so there is an increase of 25% learning outcomes from cycle I to cycle II. It can be concluded that learning the Demonstration Method can improve learning outcomes Passing for volleyball games.